Sampling plans using extended EWMA statistic with and without auxiliary information - Muhammad Naveed; Muhammad Azam; Muhammad Saeed; Nasrullah Khan; Muhammad Aslam (Kuwait Journal of Science)
In this paper, we propose an Acceptance Sampling Plan (ASP) using the statistic suggested by (Naveed et al., 2018) under the condition of known and unknown population standard deviation (SD) for the presence of with and without Auxiliary Information (AI). It is presumed that the study variable of quality trait and AI follow the bivariate normal distribution. The plan parameters of the recommended plan are discussed for all four cases under the constraint that specified producer and consumer risks are gratified.  The suggested plan is compared in term of sample size (SS) with numerous existing plans and showed that the presented plan has a smaller SS for any value of AQL, LQL. Various tables of plan parameters have been erected using various combinations of smoothing constants for industrial use. For the workable purpose, the industrial example has also been examined. At last, concluding remarks are discussed.